2017
DOI: 10.1038/mi.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with antibiotics may enhance the efficacy of fecal microbiota transplantation in ulcerative colitis: a meta-analysis

Abstract: fecal microbiota transplantation (FMT) and its challenges in treating inflammatory bowel disease (IBD). As highlighted by the authors, one of the major factors that may optimize FMT for IBD is how the recipient's bowel is prepared prior to an FMT. Theoretically, using antibiotics has the potential to ''make space for the new microbiota'' before FMT by freeing previously occupied niches.Recently, Ishikawa et al. 2 showed that administration of amoxicillin, fosfomycin, and metronidazole for 2 weeks prior to FMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 6 publications
1
50
1
1
Order By: Relevance
“…However, the pre‐FMT postantibiotic sampling was able to shed light on the changes brought by the antibiotics and their resolution with FMT. We also studied three major antibiotics together rather than one at a time, which is not usual practice but was done to ensure a better uptake as has been shown in studies of FMT in patients without cirrhosis . However, given reports that antibiotic‐associated microbial changes can last for several months to years even in healthy individuals, it is highly unlikely that these changes reverting close to preantibiotic baseline will return to normal in this much more advanced population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pre‐FMT postantibiotic sampling was able to shed light on the changes brought by the antibiotics and their resolution with FMT. We also studied three major antibiotics together rather than one at a time, which is not usual practice but was done to ensure a better uptake as has been shown in studies of FMT in patients without cirrhosis . However, given reports that antibiotic‐associated microbial changes can last for several months to years even in healthy individuals, it is highly unlikely that these changes reverting close to preantibiotic baseline will return to normal in this much more advanced population .…”
Section: Discussionmentioning
confidence: 99%
“…During this trial a pre‐FMT broad‐spectrum antibiotic course was administered in order to potentially increase the uptake of FMT. However, this also gave us an opportunity to study the impact of antibiotic therapy in this population and the changes wrought by FMT compared to standard of care (SOC) therapy . We found in the prior results that bacterial diversity was restored after FMT, but the effects of FMT on antibiotic‐associated changes in bacterial function in this population are unclear.…”
mentioning
confidence: 99%
“…Both fresh and frozen stools are used in clinics and no differences in effects have been reported . Good effects can be achieved by using antibiotics to remove the intestinal microbiota of UC patients before FMT treatment . Adverse reactions include diarrhea, cramping, belching, constipation, and aspiration pneumonia in CDI patients and high fever in UC patients .…”
Section: Gut Microbiota‐based Diagnosis and Therapiesmentioning
confidence: 99%
“…Moreover, the study in children with ERA likewise demonstrated that the post‐intervention fecal specimens were not appreciably altered by the administration of the probiotic (Table ). Perhaps, then, therapeutic probiotics need to be preceded with antibiotics in order to facilitate uptake of the probiotics, as has been suggested for fecal transplant . Indeed, GF mice had substantially improved uptake of probiotics as compared to their conventionally housed counterparts .…”
Section: Therapeutic Potential Of Microbial Alterationmentioning
confidence: 99%
“…Perhaps, then, therapeutic probiotics need to be preceded with antibiotics in order to facilitate uptake of the probiotics, as has been suggested for fecal transplant. 135 Indeed, GF mice had substantially improved uptake of probiotics as compared to their conventionally housed counterparts. 134 Finally, whether butyrate production is a viable target, despite its theoretical rationale, will be discussed below.…”
Section: Probioticsmentioning
confidence: 99%